Antioxidant role of autophagy in maintaining the integrity of glomerular capillaries. Issue 1 (2nd January 2018) - Matsuda, Jun; Namba, Tomoko; Takabatake, Yoshitsugu; Kimura, Tomonori; Takahashi, Atsushi; Yamamoto, Takeshi; Minami, Satoshi; Sakai, Shinsuke; Fujimura, Ryuta; Kaimori, Jun-ya; Matsui, Isao; Hamano, Takayuki; et al.
ABSTRACT: Autophagy is a lysosomal degradation system by which cytosolic materials and damaged organelles are broken down into basic components. To explore the physiological role of autophagy in glomerular endothelial cells (GEnCs), we compared the autophagic flux among cells in the kidney under starvation. Inhibition of autophagy by chloroquine administration significantly increased the number of autophagosomes or autolysosomes in GEnCs and proximal tubular cells, but not in podocytes, suggesting that the GEnCs exhibit substantial autophagic activity. Next, we analyzed endothelial and hematopoietic cell-specific atg5 -deficient mice ( atg5 -conditional KO [cKO] mice). Glomeruli of 4-wk-old atg5 -cKO mice exhibited slightly distended capillary loops accompanied by an accumulation of reactive oxygen species (ROS). Glomeruli of 8-wk-old atg5 -cKO mice showed a lobular pattern with thickening of the capillary loops and mesangial matrix expansion; however, the vasculature of other organs was preserved. The atg5 -cKO mice died by 12 wk of age, presumably due to pancytopenia resulting from the defect in their hematopoietic lineages. Therefore, we subjected 4-wk atg5 -cKO mice to irradiation followed by bone marrow transplantation from normal littermates. Transplanted mice recapitulated the glomerular phenotypes of the atg5 -cKO mice with no obvious histological changes in other organs. Twelve-mo-old transplanted mice developed mesangiolysis and glomerulosclerosis with significant deterioration of kidney function. Administration of N-acetyl-l-cysteine, a ROS scavenger, to atg5 -cKO mice rescued the glomerular phenotypes. These data suggest that endothelial autophagy protects glomeruli from oxidative stress and maintains the integrity of glomerular capillaries. Enhancing endothelial autophagy may provide a novel therapeutic approach to minimizing glomerular diseases.